2009
DOI: 10.7861/clinmedicine.9-4-311
|View full text |Cite
|
Sign up to set email alerts
|

Timely discharge of older patients from hospital: improving the process

Abstract: -Elderly patients represent a large number of admissions to hospital, accounting for a disproportionate number of hospital bed days. Discharge planning can improve the safety and appropriateness of discharge from hospital, and can have a positive impact on length of stay and efficiency. Despite this, discharge planning is often neglected. This review, both evidence and experience based, is provided to aid with the safe discharge of elderly patients back into the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…MDTs were used in all the included studies in an attempt to improve medication management on discharge of patients to RACFs . This is by no means a revolutionary concept, because MDTs have been shown in the past to be a vital factor in effective and safe discharge planning . All the interventions were focused on providing medication information on discharge, but only two studies also attempted to provide RACF nursing staff with a medication administration chart .…”
Section: Discussionmentioning
confidence: 99%
“…MDTs were used in all the included studies in an attempt to improve medication management on discharge of patients to RACFs . This is by no means a revolutionary concept, because MDTs have been shown in the past to be a vital factor in effective and safe discharge planning . All the interventions were focused on providing medication information on discharge, but only two studies also attempted to provide RACF nursing staff with a medication administration chart .…”
Section: Discussionmentioning
confidence: 99%
“…The need for families and patients to be involved in discharge planning and agree to the plan is critical. 16 The majority of families and patients in this study reported that they did not know or were unsure of the length of hospital stay. In fact, many patients reported that they were returning home.…”
Section: Discussionmentioning
confidence: 80%
“…Also, dispositions against medical advice cannot be uniformly described as they occur for a variety of reasons, usually with inadequate characterization. LOS categories that would be difficult to optimize are those of shorter length: drug prescription and compliance is of such short nature that it cannot be predictable or manageable; furthermore, this is the period of time when a lot of expensive drugs have to be used to treat acute medical or surgical situations [15,16] …”
Section: Discussionmentioning
confidence: 99%